THE CONTENT OF CHLOROPHYLL-Α IN THE LAKES OF THE PRIMORSKY LOWLAND OF DAGESTAN AND THEIR TROPHIC STATUS - M. M. Rasulova; A. A. Gadzhiev; A. A. Rabadanova (Юг России: экология, развитие, 2014)
Eutrophication of water bodies, especially small, has become a ubiquitous problem. In this connection the efforts of the experts is increasingly aimed at the search for the methods of monitoring, prediction and control of this undesirable and dangerous process. One of the methods to assess the level trophic status is based on the determination of the content of chlorophyll-a, which was used in integrated studies of the ecological status, and trophic status of the water bodies of the Coastal plain of Dagestan.